From the Editor-in-Chief - Churski, Paweł (Rozwój Regionalny i Polityka Regionalna, 2022)
We invite you to the Latest Publication section where our Faculty Members pres- ent their most recent papers, related directly to the issue of regional development and regional policy. In the current edition, we are publishing a monography by Anna Tobolska, Emilia Bogacka, Jan Hauke and Justyna Weltrowska entitled “Dif- ferentiation of social attitudes of students and academic teachers in Wielkopolska region during the COVID-19 pandemic”.